Differences in gene expression in Atlantic salmon parr and smolt after challenge with Piscine orthoreovirus (PRV). (May 2016) - Johansen, Lill-Heidi; Dahle, Maria Krudtaa; Wessel, Øystein; Timmerhaus, Gerrit; Løvoll, Marie; Røsæg, Magnus; Jørgensen, Sven Martin; Rimstad, Espen; Krasnov, Aleksei
Highlights: Differences in expression of immune genes in uninfected parr and smolts were small. After challenge clearance of piscine reovirus in parr was faster than in smolts. Genes related to innate antiviral and B cells responses were activated earlier in parr. Stimulation of heme and iron metabolism and erythropoiesis was greater smolts. Abstract: Heart and skeletal muscle inflammation (HSMI) are a disease of farmed Atlantic salmon ( Salmo salar ) associated with Piscine orthoreovirus (PRV). The disease appears mainly during the marine production phase. This study examined if smoltification and transfer to seawater could compromise immune responses to PRV. Parr and smolts of the same origin were challenged by cohabitation with intraperitoneally injected salmon. Peak levels of PRV in spleen of cohabitants were reached after 8 weeks, but at a lower level in parr compared to smolts. Thereafter the virus levels declined, but remained significantly lower in parr than in smolts. Both groups developed typical HSMI histopathological heart lesions, which were most prominent after 10 weeks. Microarray and qPCR analyses revealed slightly lower expression of immune genes in spleen and head kidney of smolts before challenge. Infected parr showed earlier induction of genes involved in innate antiviral immunity, as well as for genes related to B and T cell responses. Gene expression profiles also indicated stimulation of heme and iron metabolism and erythropoiesis in smolts, which may indicate replacement of PRV-infected erythrocytes.